2012
DOI: 10.1111/j.1582-4934.2011.01480.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of microRNA 20b with resveratrol and longevinex is linked with their potent anti‐angiogenic action in the ischaemic myocardium and synergestic effects of resveratrol and γ‐tocotrienol

Abstract: Resveratrol, a constituent of red wine, and γ-tocotrienol, a constituent of palm oil are important for cardioprotection. Although microRNAs are known regulators for genes involved in cardiac remodelling, the regulatory pathway involving microRNA has not been studied so far. We explored the cardioprotection by resveratrol, longevinex and γ−tocotrienol in ischaemia/reperfusion(I/R) model of rat and determined miRNA profile from isolated RNA. Systemic analyses of miRNA array and theirs targets were determined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 40 publications
5
46
0
Order By: Relevance
“…Here we revealed the role of miR-20b in the down-regulation of VEGF, which mediates vascular permeability and angiogenesis in HRECs. Using miR-20b mimic transfection, we further demonstrated that HG-induced VEGF up-regulation and subsequent functional changes, i.e., vascular permeability and angiogenesis, can be prevented by increasing the level of miR-20b in HRECs, which is consistent with the previous study showing that miR-20b has an antiangiogenic effect in the ischemic myocardium [27]. Furthermore, by using bioinformatics analytic tool and luciferase reporter assay, we identified AKT3 as a target of miR-20b.…”
Section: Discussionsupporting
confidence: 79%
“…Here we revealed the role of miR-20b in the down-regulation of VEGF, which mediates vascular permeability and angiogenesis in HRECs. Using miR-20b mimic transfection, we further demonstrated that HG-induced VEGF up-regulation and subsequent functional changes, i.e., vascular permeability and angiogenesis, can be prevented by increasing the level of miR-20b in HRECs, which is consistent with the previous study showing that miR-20b has an antiangiogenic effect in the ischemic myocardium [27]. Furthermore, by using bioinformatics analytic tool and luciferase reporter assay, we identified AKT3 as a target of miR-20b.…”
Section: Discussionsupporting
confidence: 79%
“…In 2009, Wang and colleagues reported that MiR-327 expression levels were up-regulated in type-2 diabetic rat models using a miRNA microarray [21]. Subsequently, studies have shown that miR-327 increased by 10-fold in rats with MIRI and nearly 3-fold in the kidneys of rats with renal I/R injury, respectively [22,23]. Additionally, in injured sciatic nerves, miR-327 was increased and involved in peripheral nerve regeneration by targeting CCL2 in a 3′-UTR-dependent manner [38].…”
Section: Discussionmentioning
confidence: 99%
“…I/R heart tissues and renal I/R injury models [21][22][23]. A search using the public prediction algorithm TargetScan (http://www.targetscan.org/) shows that RP105 is a possible target gene of miR-327.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…The upregulated miRNAs included miR-20b and miR-21 (antiangiogenic), which are implicated in cardiac remodeling. These data suggest that resveratrol exerts a significant cardioprotection through miRNA modulation [69,70]. …”
Section: Modulation Of Mirna Expression By Natural Agentsmentioning
confidence: 99%